Antimicrobial Profiling of Bacteria Isolated from Fish Sold at Informal Market in Mufakose, Zimbabwe - Claudious Gufe; Tinashe Canaan Hodobo; Bernard Mbonjani; Otlia Majonga; Jerikias Marumure; Shuvai Musari; Gilbert Jongi; Pious Vengesayi Makaya; Jairus Machakwa (International Journal of Microbiology)
The number of infections caused by antibiotic resistant bacteria is rising worldwide. Fish from multisource pollution waters can harbour multidrug-resistant bacteria that can be disseminated to humans through eating or contact of contaminated fish. A cross-sectional study was carried out to (i) isolate and phenotypically identify bacteria from 36 fish samples from informal market in Mufakose, Harare, and (ii) determine the antibiotic sensitivity pattern of the isolated bacteria against ten available antibiotics (ampicillin 10 μg, gentamycin 30 μg, penicillin G 10 μg, erythromycin 15 μg, tetracycline 30 μg, kanamycin 30 μg, neomycin 10 μg, cloxacillin 5 μg, lincomycin 15 μg, and sulfamethoxazole 25 μg) using the Kirby–Bauer disk agar diffusion method. Eight bacterial genera were isolated and identified, and they were Escherichia, Aeromonas, Staphylococcus, Pseudomonas, Citrobacter, Klebsiella, Enterobacter, and Proteus. Among the isolates, Escherichia coli was isolated most frequently (44%) followed by Staphylococcus aureus (19%), Enterobacter aerogenes (7%), Aeromonas spp. (5%), Proteus mirabilis (5%), Citrobacter (5%), and coagulase-negative Staphylococci (5%) and the least frequent were Klebsiella (3%) and Pseudomonas (3%). All isolates were susceptible to gentamycin. Varying antibiotic resistance rates were observed to lincomycin (100%), ampicillin (81%), penicillin (67%), erythromycin (65%), tetracycline (63%), neomycin (61%), cloxacillin (43%), kanamycin (24%), and sulphamethoxazole (13%). All the isolates were multidrug-resistant (resistant to at 3 or more drugs tested) except Proteus mirabilis. Proteus mirabilis has multiple antibiotic resistance (MAR) index of 0.2, and the other isolated bacteria had MAR indexes greater than 0.2 ranging from 0.3 to 0.7. Those MAR indexes above 0.2 showed that the bacteria isolates are from a high risk source where antibiotics were frequently used, possibly from sewage effluents. Isolation of enteric bacteria such as Escherichia coli is an indication of faecal contamination, and this poses a high risk to animal and human health. These significant findings call for effective risk assessment models and management plans that protect human, animal, and environmental health.